Dear enemies or nasty neighbors? Causes and consequences of variation in the responses of group-living species to territorial intrusions - Christensen, Charlotte; Radford, Andrew N (Behavioral ecology, 2018)
Responses of territorial groups to intruders depend on rival identity. We explore reasons for variation in responses to neighbors versus strangers arising between species, social and ecological conditions, and group members. We also consider the potential consequences of this variation for group dynamics, collective decisions, and individual benefits and costs. Finally, we suggest theoretical modeling, hormonal mechanisms, and man-made disturbances as avenues of future research that would enhance our understanding of group-territorial behavior and sociality. Abstract Territorial behavior is widespread throughout the animal kingdom, with responses to conspecific intruders differing depending on various ecological, life history, and social factors. One factor which has received considerable research attention is rival identity. Early work provided many examples of species exhibiting relatively stronger responses to strangers versus neighbors (the “dear-enemy” effect) or the opposite (the “nasty-neighbor” effect). However, those studies focused predominantly on single or pair-bonded territory-holders. There is increasing evidence of neighbor–stranger response differences in group-living species (where 3 or more individuals share a territory), and of within-species variation in the relative responses shown to these 2 intruder types. Considering social species is important both because group territoriality is widespread and because group responses include the actions of multiple individuals whose interests and motivations differ. We begin our review with a summary of territoriality in group-living species. We then discuss causes of variation in territorial responses depending on intruder neighbor–stranger identity, considering both between-species differences and those within species arising from context-dependent variation and from individual group members responding differently to the same intrusion. We next detail the consequences of different territorial responses, in terms of both postinteraction behavior and individual benefits and costs. Finally, we suggest 3 key areas—theoretical modeling, hormonal mechanisms, and anthropogenic disturbances—that could be developed when considering the relative responses of territory-holders to neighbors and strangers. Since conflict is a powerful selective force, determining the causes and consequences of variation in group-territorial behavior is important for a full understanding of sociality.